PUNISHING THE FAILURE TO COMPLY WITH STATUTORY DUTIES IN THE EVENT OF AN ACCIDENT - Shannon Hoctor (Obiter, 2022)
Drivers of vehicles on public roads have long been subject to various duties upon being involved in a collision or an accident. It seems that the earliest formulation of a duty upon a driver involved in an accident was promulgated in Durban in 1906, where hit-and-run motorists were targeted, with the same regulation being promulgated a year later in Pietermaritzburg. This regulation required the driver of a motor car, if an accident occurred involving a pedestrian, a person on horseback or in a vehicle, or to any horse or vehicle in the charge of a person, to stop and, if required, to give his name and address, the name and address of the owner of the motor car and its registration mark and number. The obligation to stop, to provide name and address and registration number, was repeated in the provincial ordinances which replaced these local regulations. The duties presently imposed on a driver in the event of an accident  are set out in section 61 of the National Road Traffic Act 93 of 1996 (hereinafter “the Act”). The current formulation is substantially similar to its antecedents, in the form of section 135 of the uniform Road Traffic Ordinance of 1966 (in which the traffic rules of the then four provinces of the Republic of South Africa were set out (hereinafter “the Ordinance”); for a discussion of this section and the relevant case law, see Cooper Motor Law Volume I (1982) 486ff; and s 118 of the Road Traffic Act 29 of 1989 (hereinafter “Road TrafficAct”)). The most substantial change between the various formulations was the inclusion in the Road Traffic Act of section 118(2A), in terms of section 20 of Act 39 of 1993. This provision is found in the present formulation at section 61(3). Section 61(1) creates seven separate offences, thus consequently, where an accused has knocked down and injured or killed a pedestrian and has failed to comply with the provisions of section 61(1)(a) and section 61(1)(b) he or she may be charged with contravening both of these sections. Two further offences are created in section 61(2) and section 61(3), relating to the removal of a vehicle which has been involved in an accident, from the scene of such accident. It is not unknown for a driver who has collided with another vehicle, orpedestrians, to seek to evade civil or criminal liability by fleeing the scene of NOTES/AANTEKENINGE 333 the accident in order to escape identification. Such “hit-and-run” driving, besides defeating the proper course of justice, often involves a callous disregard of the physical injuries suffered by the victims of collisions. Legislatures seek to inhibit such conduct by imposing upon the driver of any vehicle involved in accidents the duty to stop and render such assistance as may be appropriate and to report the accident. Given that the “hit and run” offence has been variously described as “one of the most serious of offences in which a motorist can become involved” (S v Mavridopolos 1973 2 SA 44 (RA) 45H), “almost invariably despicable and mean” (R v Chipunza 1967 3 SA 589 (RA) 590F-G), and “the meanest type of case it is possible for a motorist to be concerned in” (R v Pather 1942 NPD 247 248), it is proposed to examine the sentencing guidelines in relation to punishment of the failure to fulfil the duties imposed by section 61. The note will first briefly advert to each of the individual duties, before concluding with some general comments about the sentencing regime established in the Act.